Elite bilingual education in Brazil: an applied linguist’s perspective - Liberali, Fernanda Coelho; Megale, Antonieta (Colombian Applied Linguistics Journal, 2016)
This paper (i) presents the current globalized multicultural context, which supports the interest in the area, and relates its connection with bilingual education; (ii) discusses and problematizes bilingual education in Brazil from the perspective of applied linguistics and (iii) analyzes research and activities carried out in the Brazilian context. Having as a starting point Brazilian bilingual school curricula, texts taken from websites of bilingual schools, and materials related to these schools’ language allocation provided by publishers, this study analyses the type of bilingualism aimed at these schools and the type of bilingual education implemented. We also analyzed the research conducted in the area through the abstracts from the communications presented in conferences, articles and thesis in which bilingual education was the theme to identify the conception used. We adopt the theoretical framework followed by applied linguists such as Abello-Contesse (2013), Hornberger (1991, 2000), García (2009), and García and Wei (2014), which challenges monolingual conceptions of languages and monoglossic types of bilingual education. The results point to the fact that all the curricula and related materials analyzed from these schools reveal a monoglossic view of language. As for the research produced at universities, the vast majority of these productions have heteroglossic views of language as a theoretical background. Therefore, although heteroglossic views of language have been studied and discussed in the university, these discussions and findings are far from the reality of the schools in Brazil.